Identifikasi Sarana dan Prasarana Pariwisata Terhadap Kenyamanan Pengguna Wisata Pantai Jangka Kabupaten Bireuen - Aris Munandar; Fitri Muliani; Yusuf Aulia Lubis (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2023)
Jangka Beach Tourism, located in Jangka Sub district, Bireuen Regency, is a tourist attraction with a beach and culinary feel. This beach area offers the charm of an exotic beach with brownish sand and a diversity of culinary tourism around the beach. The problem that occurs in Jangka beach tourism areas is that user comfort regarding some of the facilities that have been provided is not complete and does not comply with the standards of the Regulation on Regional Minimum Service Standards, so evaluation needs to be carried out, especially from users and the public who carry out activities at tourist locations. The method used is a qualitative method that focuses on existing facilities and infrastructure at Panjang Beach by means of observation, distribution of questionnaires and literature studies related to the research topic. The results obtained from the existing infrastructure were 13.0% who said it was very satisfactory, 56.5% said it was fulfilled and 30.04% said it was not yet fulfilled. In general, 70.6% said they agreed, however, other answers related to the importance of additional facilities and infrastructure stated it was very necessary, 34.8% said it was necessary. 56.6%, 8.7% is enough, so the facilities and infrastructure that still need to be completed are not enough, such as accommodation, banking system, health, educational facilities and sports advice. The conclusion is that the long-term beach comfort is adequate, it's just that the facilities and infrastructure need to be improved so that it becomes an attraction for tourists.